The Implications of Climate Change for States and Corporations - Hussain, Zakir (Graduate Journal of Pakistan Review (GJPR), 2021)
This research paper will discuss that what are the implications of climate change for states and corporations? Than further I have discusses in what ways climate change has affected the human life at one place it has violated the rights of human and at the same time humans has not taken it as their responsibility to protect it, but they have either destroyed the climate change whether they are the industrialists or a common man. After that I have seen that this issue is politicized and some big powers really don’t want to solve to this issue because of their interests. Since, it is crystal clear that the temperature is rising time to time because of large number of greenhouse carbon emission. And states are involved in protecting the big emitters. This proposal is significant for the study of state relations with industries and big corporations, in term of global climate change. While writing this proposal I have in mind that we are living in an age where Liberalization, Privatization and Globalization are the key influential factors of the global politics. It could become an economic and environmental security issue for all states. I have used critical theory to analyze the inputs which were qualitative type of data. Beyond that I will take some of the international and regional countries as examples and see their roles in effecting or protecting the climate. The issue is well addressed before but many states are not interested to think on it out of short term interests. What I have found among the many issues is that there is always understanding between the state and the industries that emit greenhouse carbon in developed and developing countries which is difficult to be solved because they have state as their protectors so there is a big need of public action to tackle the issue. For, at least they can avoid their part of greenhouse carbon emission. The window of room to prevent climate change dangers is closing very fast and in some states it is alarming.